Sharing literature with children : a thematic anthology - Butler, Francelia, 1913-1998. (Prospect Heights, IL : Waveland Press, 1989)
A thematically arranged anthology of folklore, myths, fiction, poetry, biographies, and essays.
Includes bibliographical references.
Keywords: Children's literature